Special Study: Constructions for building over water - Featherstone, Lester Burritt (School of Architecture, Planning and Geomatics, 2021)
Building over water presents a certain major problem. This problem is concerned with the foundations, which are, in the case of the proposed Anglers' River Resort, to be in the Kromme River Bed. The construction of the superstructure presents no special problems, being the same as those encountered on land. Thus this. study will be concerned with the type of foundation required to support the building over the water.